Pengabdian Pendampingan Manajemen Usaha UMKM Sambel Pecel Bu Heru Untuk Meningkatkan Daya Saing : Pendampingan Manajemen Usaha UMKM Sambel Pecel Bu Heru Untuk Meningkatkan Daya Saing - DIAN ANITA (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Competitiveness is important for MSMEs to be able to develop and survive in the midst of competition. Efforts to strengthen MSMEs can be done by collaborating with university service programs. In the service program carried out by STIE YPPI Rembang through the KKU (Business Work Course) program located at the Sambel Pecel MSME, Bu Heru. The problems that occur in the MSME Sambel Pecel Bu Heru are the marketing area is still limited, the marketing media is not maximized, does not have business legality and there are no clear directions for the location. Based on these problems, a service program was prepared, namely training and assistance in the creation and use of social media, expansion of marketing areas, facilitation of business legality management and the creation of google map features. The results of the KKU STIE YPPI Rembang are MSME Sambel Pecel Bu Heru has an Instagram social media account, has an MSME location on the google maps application, creates a photo catalog for promotion and has a business license.